Weed suppression in the formation of brachiarias under three sowing methods - S.F. Lima; P.C. Timossi; D.P. Almeida; U.R. Silva (Planta Daninha, 2014)
The success of conservation systems such as no-till depends on adequate soil cover throughout the year, which is possible through the use of cover crops. For this purpose the species belonging to the genus Urochloa has stood out by virtue of its hardiness and tolerance to drought. Aiming ground cover for the no-till system, the objective was to evaluate the establishment of two species of the genus Urochloa, in three sowing methods, in the weed suppression and the sensitivity of these forages to glyphosate. The study design was a randomized block with a 2 x 3 x 3 factorial arrangement, in which factor A was composed of Urochloa ruziziensis and Urochloa hybrid CIAT 36087 cv. Mulato II, factor B was formed by sowing methods: sown without embedding, sown with light embedding and sown in rows, and factor C was composed of three doses of glyphosate (0.975, 1.625 and 2.275 kg ha-1 of acid equivalent). For determination of weed suppression, assessment of biomass yield and soil cover was performed, by brachiaria and weeds, at 30, 60, 90, 120 and 258 days after sowing. Visual assessment of the desiccation efficiency at 7 and 14 days after herbicide application was performed. It is concluded that embedding Urochloa seeds stands out in relation to sowing in the soil surface. Urochloa ruziziensis is more efficient in the dry weight yield, weed suppression, in addition to being more sensitive to glyphosate herbicide.